Cross-Regional Elemental Comparison of Mussels Using Total Reflection X-Ray Fluorescence (TXRF) - Nina-Nicoleta Lazăr; Ira-Adeline Simionov; Mădălina Călmuc; Valentina-Andreea Călmuc; Cătălina Iticescu; Puiu-Lucian Georgescu; Mihaela Timofti; Silvia Drăgan (Molecules)
This study evaluates the effectiveness of Total Reflection X-ray Fluorescence for multi-element analysis in mussels, focusing on sensitivity, precision, and detection limits. Additionally, it offers a cross-regional comparison of elemental composition in mussels from aquaculture farms in Italy, Spain, and Chile. TXRF, using suspensions of mussel samples, proved effective in detecting minor and trace elements, with recovery rates over 80% for Fe, Cu, Zn, As, and Sr. The research offers a chemical element comparison of Mytilus galloprovincialis and Mytilus chilensis mussels, revealing significant variation based on geographic origin. Correlation matrices demonstrated variable associations between elements, indicating that regional environmental conditions influence bioaccumulation. These findings deepen our understanding of how mussels accumulate elements in different environments. However, further research is needed to develop comprehensive elemental databases and to account for seasonal and temporal variations in mussels’ elemental composition. This study may bring insight for food safety and public health monitoring.